2006
DOI: 10.1038/sj.onc.1209501
|View full text |Cite
|
Sign up to set email alerts
|

Identification of STAT3 as a specific substrate of breast tumor kinase

Abstract: Breast tumor kinase (Brk) is a non-receptor tyrosine kinase distantly related to the Src family kinase. It is expressed in more than 60% of breast tumors, but the biological role of this kinase remains to be determined. Only a limited number of substates have been identified for Brk, and the link of Brk to tumorigenesis remains largely unknown. In this study, we provide evidence that the signal transducer and activator of transcription 3, STAT3, is a physiological target of Brk. Activation of STAT3 previously … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
98
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(104 citation statements)
references
References 53 publications
6
98
0
Order By: Relevance
“…In addition, here, we could show that also PTEN, which belongs to the same PI3K/Akt signalling pathway, coprecipitates with PTK6 in T47D cell line, and is statistically associated with the expression of PTK6 in tumour tissue. PTK6 influences the MAPK pathway (as described above), and there is evidence that STATs are also physiological targets of PTK6 (Liu et al, 2006;Weaver and Silva, 2007). This obvious involvement of PTK6 in all three signalling pathways may be explained to some extent by cross talk between pathways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, here, we could show that also PTEN, which belongs to the same PI3K/Akt signalling pathway, coprecipitates with PTK6 in T47D cell line, and is statistically associated with the expression of PTK6 in tumour tissue. PTK6 influences the MAPK pathway (as described above), and there is evidence that STATs are also physiological targets of PTK6 (Liu et al, 2006;Weaver and Silva, 2007). This obvious involvement of PTK6 in all three signalling pathways may be explained to some extent by cross talk between pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Knockdown of PTK6 decreases proliferation in breast cancer cell lines (Harvey and Crompton, 2003) and blocks activity of a GTPase, of ERK5 (extracellular signal-regulated kinase) and p38 mitogenactivated protein kinase (MAPK), but not Akt (Mitchell et al, 1994;Barker et al, 1997;Llor et al, 1999;Born et al, 2005;Ostrander et al, 2007). Furthermore, PTK6 phosphorylates STAT3 (signal transducer and activator of transcription 3; Liu et al, 2006) and STAT 5b, leading to increased STAT 5b transcriptional activity in several breast cancer cell lines (Weaver and Silva, 2007).…”
mentioning
confidence: 99%
“…We next tested whether activation of Brk is required for a direct interaction with STAP- Importantly, recent studies have shown that STAT3 is a Brk substrate and that Brk activates STAT3 [17]. STAT3 is known to act as an oncogene in a constitutively active form, and phosphorylation and activation of STAT3 is correlated with breast cancer [18,19,20].…”
Section: The Kinase Activity Of Brk Is Required For a Direct Interactmentioning
confidence: 99%
“…STAT3 and STAT5, which play crucial roles in cell proliferation and differentiation, are also believed to be activated by BRK (Liu et al, 2006;Weaver and Silva, 2007). Our previous studies demonstrate that STAP-2 interacts with and influences several signaling molecules, including STAT3 and STAT5.…”
Section: Interactions Of Stap-2 With Brk and Stat3/5mentioning
confidence: 99%
“…BRK substrates include RNA-binding proteins (Sam68 (Coyle et al, 2003;Derry et al, 2000;Lukong et al, 2005), SLM-1/2 (Haegebarth et al, 2004), and the polypyrimidine tractbinding protein-associated splicing factor (PSF) (Lukong et al, 2009)), transcription factors (STAT3 (Liu et al, 2006) and STAT5A/B (Weaver and Silva, 2007)), adaptor molecules (STAP-2) (Mitchell et al, 2000), and a variety of signaling molecules (paxillin (Chen et al, 2004), p190RhoGAP (Shen et al, 2008), kinesin-associated protein 3A (KAP3A) (Lukong and Richard, 2008), Akt (Zhang et al, 2005), -catenin (Palka-Hamblin et al, 2010), and ARAP1 (Arf-GAP, Rho-GAP, ankyrin repeat and PH domain-containing protein 1; also known as centaurin δ-2) (Kang et al, 2010)). Although BRK expression is known to induce tyrosine phosphorylation in some of these, similar actions in others have yet to be confirmed.…”
Section: Substrates Interacting Proteins and Activationmentioning
confidence: 99%